2022
DOI: 10.3390/jpm12060946
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Allergen-Specific Immunotherapy in ENT Diseases: A Systematic Review

Abstract: Previous studies have demonstrated that both subcutaneous (SCIT) and sublingual specific immunotherapy (SLIT) are effective in treating allergic rhinitis (AR). Further studies have evaluated the efficacy of allergen-specific immunotherapy (AIT) on different ear, nose, and throat (ENT) manifestations, in which allergy might have an etiopathogenetic role, such as local allergic rhinitis (LAR), rhinosinusitis (RS), otitis media (OM), and adenotonsillar (AT) disease. Nevertheless, the management of allergy in ENT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 121 publications
1
5
0
Order By: Relevance
“…Subcutaneous immunotherapy (SCIT) or sublingual immunotherapy (SLIT) against pollen is strongly recommended for seasonal allergic rhinitis induced by pollen. 93 For pollen-induced asthma, SCIT reduces asthma symptoms and asthma medications, with lower evidence for SLIT. 94 However, it is a key question whether the changes in pollen allergenicity will affect the efficacy of immunotherapy.…”
Section: What Is Known About Therapy and Prevention For Pollen Asthma?mentioning
confidence: 99%
See 1 more Smart Citation
“…Subcutaneous immunotherapy (SCIT) or sublingual immunotherapy (SLIT) against pollen is strongly recommended for seasonal allergic rhinitis induced by pollen. 93 For pollen-induced asthma, SCIT reduces asthma symptoms and asthma medications, with lower evidence for SLIT. 94 However, it is a key question whether the changes in pollen allergenicity will affect the efficacy of immunotherapy.…”
Section: What Is Known About Therapy and Prevention For Pollen Asthma?mentioning
confidence: 99%
“…Other therapies such as anti‐IL5/IL5Rα receptor or anti‐IL4Rα antibodies may also be considered with evidence of Type 2 inflammation. Subcutaneous immunotherapy (SCIT) or sublingual immunotherapy (SLIT) against pollen is strongly recommended for seasonal allergic rhinitis induced by pollen 93 . For pollen‐induced asthma, SCIT reduces asthma symptoms and asthma medications, with lower evidence for SLIT 94 .…”
Section: State Of Artmentioning
confidence: 99%
“…It has been suggested that the comorbid AR and its associated type 2 inflammatory response may amplify the CRS disease process. 21 Several prospective studies have shown that the addition of allergen immunotherapy to standard CRS treatment is associated with decreased nasal symptom scores, improved radiologic outcome scores, and, in one study, a 54% decrease in sinus surgeries. [21][22][23]…”
Section: Ar and Crswnpmentioning
confidence: 99%
“…21 Several prospective studies have shown that the addition of allergen immunotherapy to standard CRS treatment is associated with decreased nasal symptom scores, improved radiologic outcome scores, and, in one study, a 54% decrease in sinus surgeries. [21][22][23]…”
Section: Ar and Crswnpmentioning
confidence: 99%
“…Some factors, such as allergy and infection, are thought to be involved in the development of OME. 8 Therefore, atopic condition and infection are probably the risk factors of OME in children with AH and it is warranted to further study.…”
Section: Introductionmentioning
confidence: 98%